Classification of ecosystem long term observation data product - Wen SU; Li ZHANG; Xuebing GUO; Honglin HE; Xinzhai TANG; Xiaoli REN (大数据)
The long-term ecosystem observation can provide data of water, soil, meteorology and biology to support ecosystem evaluation and management.At present, there is a lack of long-term observation data product system of ecosystem in China, so no effective guidance can be provided for the production of data products.Firstly the data product system of international eco-environmental research networks was analyzed.Then a long-term observation data product system of ecosystem based on the data product classification, data product gradation two dimensions was proposed, combining the existing long-term observation protocols and data resources of ecosystem in China.It could not only express the content of long-term observation data products, but also the process of data product production and processing, and had been applied to design the long-term observation data product system of forest ecosystem of Chinese ecosystem research network (CERN).This data product system has good practical value and will play an important role in improving the value of long-term observation data.